In-Service Teacher Education Programmes: Issues and Challenges - Piplani, Himanshi; Chopra, Shruti (INDIAN EDUCATIONAL REVIEW, 2017)
Teacher professional development is an integral part of educational reforms as highlighted in various educational policies and commission reports including National Policy of Education (1986) and Kothari commission (1964–66). This paper presents a study of in-service teacher education programmes and the perceptions of 30 teachers from government schools and private schools. The data, collected through responses elucidated in interviews, were qualitatively analysed using a framework designed by the researchers. The findings highlight the factors that contribute or hinder the implementation of the in-service teacher education programmes and the need for moving beyond the traditional model of in-service teacher training. Further, the study draws upon suggestions for re-designing in-service programmes.